Gramáticas de lo inaudito as Decolonial Grammars: Notes for a Decolonization of Listening. - Acosta López, María del Rosario (Research in Phenomenology, 2022)
This paper proposes to reflect self-critically on an ongoing research project entitled "Grammars of listening," which started as a philosophical approach to the question of listening at the site of trauma and the challenges this kind of listening poses to our conceptions of memory and history, and has recently shifted to asking about the possible limitations to such a reflection when confronted with a decolonial perspective on temporality. I start by presenting a conceptual background for my inquiry, and asking what kind of listening is required when trauma is considered as a colonizing form of violence – that is, when its effects are not only understood as an assault on life but on the conditions of production of sense that make life legible. Following the kind of challenges that such an understanding of trauma poses to the responsibility to listen to its testimony, the paper moves on to propose that only a decolonial approach to listening can truly do justice to the task of rendering testimonies of traumatic violence audible. By decolonizing the frameworks that organize and determine colonial and colonizing distributions of sense, I propose that grammars of lo inaudito understood as decolonial grammars contribute to resisting and disorganizing the criteria for legibility and audibility that colonizing forms of violence not only institute but constantly actualize in their attempt to perpetuate their silencing power.